Ultra-Low Contrast Percutaneous Coronary Intervention Guided by Optical Coherence Tomography Complicated by Coronary Perforation - Harding, Scott A. (JACC Case Rep, 2020)
Percutaneous coronary intervention (PCI) in patients with chronic kidney disease is associated with a high-risk of contrast-induced nephropathy. We describe a case of ultra-low contrast PCI guided using optical coherence tomography using normal saline for clearance complicated by distal wire perforation treated with embolization. (Level of Difficulty: Intermediate.)